Application of Collaborative Cultural Maps to Improve Critical Thinking Skills - Indawati, Ninik; Wiraningsih, Hesti; Mulyanti, Windra Septi (Actual Insight, 2025)
Critical and collaborative thinking skills are essential 21st-century competencies for learners in facing global challenges. Unfortunately, the learning of Natural and Social Sciences (IPAS) in elementary schools is still dominated by the rote approach, without encouraging understanding of the meaning of local cultural values. This research aims to apply the Collaborative Cultural Map model to improve the critical and collaborative thinking skills of grade IV students. The research uses the Kemmis and McTaggart model Class Action Research (PTK) approach which was carried out in two cycles at SD Negeri X Malang in the even semester of 2024/2025, with 27 students. Data was collected through observation, pre-post tests, interviews, and documentation, then analyzed descriptively, quantitatively, and qualitatively. The results showed an increase in students' learning completeness from 74.07% in the pre-cycle to 88.89% in the first cycle, and reached 100% in the second cycle, with an average final score of 93.33. In addition to academic improvement, this model encourages active participation, effective communication, and better social interaction in the classroom. These findings prove that collaborative learning based on local culture effectively strengthens 21st century skills and makes an innovative contribution to the development of more contextual science learning models in primary schools.